1982
DOI: 10.1037/0021-843x.91.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Depression and cognitive characteristics of stressful life-event types.

Abstract: Stressful life events as well as individual appraisals have been hypothesized as important antecedents of depression. However, the examination of characteristics of life events has been a relatively neglected topic. The present study investigated depression and life-event characteristics by applying an event classification scheme proposed by Fairbank and Hough (1979). Cognitive appraisal properties of event types were also examined to shed light on event qualities. Four hundred undergraduates completed the Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…Research among adolescents and adults shows a significant association between stressful life events and depression or depressive symptoms [35, 36]. However, many depressed youth do not experience a stressful life event prior to their depression and not all youth who experience stressful or adverse life events become depressed.…”
Section: Introductionmentioning
confidence: 99%
“…Research among adolescents and adults shows a significant association between stressful life events and depression or depressive symptoms [35, 36]. However, many depressed youth do not experience a stressful life event prior to their depression and not all youth who experience stressful or adverse life events become depressed.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that negative, uncontrollable perceived events had stronger ad verse effects on psychological health than negative, controllable ones (Husaini & Neff, 1980;McFarlane, Norman, Streiner, Roy, & Scott, 1980), whereas others have not (Fontana, Hughes, Marcus, & Dowds, 1979;Sandler & Lakey, 1982). Whereas individuals who tended to per ceive events as being due to chance (i.e., uncontrollable) showed more depressive symptoms in one study , Type C events (that were seen as uncontrollable) were least associated with depres sion in another (Hammen & Mayol, 1982). In general, however, it ap pears that uncontrollable events tend to correlate higher with the amount of illness than controllable ones do (Stern, McCants, & Pettine, 1982;Suis & Mullen, 1981).…”
Section: Perceptions Of Controlmentioning
confidence: 99%
“…This confounding of aspects of events and attributional style could have produced the results. Others have noted that some events do tend to have commonly shared appraisals (Hammen & Mayol, 1982).…”
Section: Attributlonal Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations